Peran Pendidikan Islam Dalam Mengatasi Krisis Moral Generasi Z Di Era Globalisasi Digital - Cantri Maesak; Opik Taupik Kurahman; Dadan Rusmana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The moral crisis experienced by Generation Z in the digital era is a major challenge triggered by globalization and rapid technological developments. This generation is often influenced by digital culture which can shift important moral values. Education, especially Islamic education, plays a key role in overcoming this problem by instilling moral values, digital ethics and social responsibility. Islamic education can help shape the character of the younger generation by equipping them with strong morality, critical thinking, and the ability to navigate the digital world wisely. Therefore, it is important to integrate moral and spiritual education so that generation Z can face it with integrity and wisdom. Islamic education that prioritizes faith and ethical values ​​has the potential to be the main solution in facing this moral crisis